The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1152/ajpheart.00461.2014
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal comparison of hemodynamics and intraluminal thrombus deposition in abdominal aortic aneurysms

Abstract: (ILT), which complicates AAA progression and risk of rupture. Patient-specific computational fluid dynamics modeling of 10 small human AAA was performed to investigate relations between hemodynamics and ILT progression. The patients were imaged using magnetic resonance twice in a 2-to 3-yr interval. Wall content data were obtained by a planar T1-weighted fast spin echo black-blood scan, which enabled quantification of thrombus thickness at midaneurysm location during baseline and followup. Computational simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…Velocity data was obtained from computational fluid dynamics (CFD) simulations of blood flow in two patient-specific AAA models, as described in Arzani et al (2014b). The vascular models spanned from the descending aorta through the iliac arteries to ensure the region of interest (aneurysm) was sufficiently far from inflow and outflow boundaries.…”
Section: Methodsmentioning
confidence: 99%
“…Velocity data was obtained from computational fluid dynamics (CFD) simulations of blood flow in two patient-specific AAA models, as described in Arzani et al (2014b). The vascular models spanned from the descending aorta through the iliac arteries to ensure the region of interest (aneurysm) was sufficiently far from inflow and outflow boundaries.…”
Section: Methodsmentioning
confidence: 99%
“…Six patient-specific AAA models were used in this study and WSS data was obtained from computational fluid dynamics (CFD) simulations using the software package SimVascular (simvascular.org), as described in [5]. The models were constructed from magnetic resonance imaging and started from the supra celiac aorta and continued to the iliac arteries, including the major branch arteries.…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
“…As a means to quantify this behaviour in transient simulations of blood flow, the time-averaged wall shear stress (TAWSS) and the oscillatory shear index (OSI) [34] are often used to measure the interaction between the flow field and the artery wall (i.e. [5,[35][36][37][38]). Doyle et al showed, via a serial CFD study of a patientspecific AAA over 2.5 years, the direct spatial relationship between low TAWSS, local aneurysm expansion and localised in vivo ILT development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Doyle et al showed, via a serial CFD study of a patientspecific AAA over 2.5 years, the direct spatial relationship between low TAWSS, local aneurysm expansion and localised in vivo ILT development [5]. However, it should also be noted that despite thrombotic susceptibility typically being associated with low TAWSS and high OSI, O'Rourke et al [37] and Arzani et al [38] identified that regions of low OSI had a good correlation with the site specificity of ILT within aneurysms.…”
Section: Introductionmentioning
confidence: 99%